“Out for Delivery”: Pleasure and Suffering in the Work of Application Deliverers - Marcos Vinícius Martins Maciel; Luis Eduardo Brandão Paiva; Rafaela de Almeida Araújo; Tereza Cristina Batista de Lima (Revista de Administração IMED, 2022)
This research aimed to investigate the causes of pleasure and suffering of application deliverers. The study stands out for promoting the understanding of the work context that gives rise to the main causes of physical and mental illness of application deliverers, providing subsidies for the psychodynamics of work, for the construction and analysis of demand and for the service given the increase in this group of workers. This is a qualitative research, carried out through semi-structured interviews with 11 agents. The interview script was inspired by the scale of indicators of pleasure and suffering at work and the assessment scale of work-related harm, both belonging to the inventory on work and risks of illness, prepared by Mendes and Ferreira (2007). The results indicate that work provides both pleasure and suffering, although situations stand out in which delivery men expose feelings of suffering associated with the activity they perform. The main motivations are survival and lack of bureaucracy to start the activity, even though there are no labor rights and guarantees. The damage caused by work is related to the high emotional cost, lack of motivation, desire to give up the activity, loneliness and pain in the body and head. This study contributes to the scientific field of pleasure and suffering at work, emphasizing that there is a need for public policies to formalize this category of work to guarantee its basic needs.